(3GdJehjd GdNGQLj hCKQg Ydi GdaLhGJ GdEbJUGOjIs - (3SGeQ Ydj(B, (3YHO GdgGOjs ((3YeGf(B:s (3OGQ GdGCjGe(B,s, 2015)
(3GdGWGQ GdYGe ddOQGSI jVe GdGWGQ GdfXQj dOQGSI GdJehjd GdNGQLj aj GdCQOf hGdJMdjd GdbjGSj dCKQ GdJehjd GdNGQLj Ydi GdaLhGJ GdGbJUGOjI aj GdCQOf h UhdG Gdi GdfJGFL hGdJhUjGJ(B.s
(3GdeQGLY U(B.179s
Keywords: (3GdJehjds; (3GdJehjd GdOhdjs; (3GdJehjd(B- (3GdCQOfs; (3GdbQhVs